MWIR narrowband filter based on guided-mode resonance subwavelength structure - He-Zhuang Liu; Jiang Wu (Journal of Electronic Science and Technology)
This work proposes a novel design for a narrowband filter operating in the mid-wave infrared (MWIR) spectrum. The filter is designed with a single layer of slab waveguide decorated with ariy layer of gold grating arrays. This design demonstrates superior narrowband transmission properties within the MWIR range, which can be explained in the framework of guided-mode resonance (GMR). Since MWIR spectral data is crucial for identifying the chemical fingerprint of man-made objects and natural materials, the GMR filters hold great potential in integration with commercial MWIR photodetectors and focal plane arrays (FPAs) and addressing the market's demand for ultra-compact spectral detection solutions. Theoretical studies have investigated the influential parameters in the GMR filter design and provided the methods towards optimal filtering performance. The center wavelength of these transmission filters exhibits significant tunability, spanning from 3 ​μm to 5 ​μm across the MWIR spectrum, while the full width at half maximum (FWHM) exhibits remarkable variability, ranging from 5.7 ​nm to 101.0 ​nm, enabling the attainment of desired filter performance contingent upon judicious waveguide material selection and optimized structural design. This work forges a path toward integrating multifunctional capabilities into ultra-compact MWIR sensors.